Application Research on Three-dimension Design of Gate Station Engineering Based on BIM Technology - LI Rang; HUANG Jinpeng; HU Xubao; CHEN Weihua; ZHANG Zhouwen (Renmin Zhujiang)
With the continuous promotion of BIM technology in civil and hydraulic engineering in China,the civil and hydraulic design industry has ushered in a new wave of technologies.Given the typical gate station projects in the Pearl River Delta region,the design and application research based on BIM is carried out.The concept of BIM technology and its application status in the water conservancy and hydropower industry are analyzed.Besides,the preparatory work before carrying out BIM design for gate station projects is described,and the various applications of BIM design such as parametric modeling,calculation and analysis,drawing and quantity,and scheme reporting are also introduced.Through this practice,the effectiveness of BIM technology in gate station engineering design is verified,which provides BIM application ideas for related engineering projects.